Incidental Findings Diagnosed during Preprocedural Evaluation of TAVR. (2nd April 2019) - Sahiner, Levent; Coteli, Cem; Kivrak, Ahmet; Sener, Yusuf Ziya; Asil, Serkan; Hazirolan, Tuncay; Kaya, Ergun Baris; Ozer, Necla; Aytemir, Kudret
Abstract : Introduction . Transcatheter aortic valve replacement is an important therapeutic option for aortic stenosis (AS) patients who have high surgical risk. TAVR is a complex procedure. Proper preparation of the patient is of significant importance for the final success and affects the morbidity and mortality of the TAVR directly. Pre-TAVR computed tomography is one of the corner stones of these preparation steps, and many patients get some incidental diagnoses. Materials and Methods . In this trial, we have investigated 155 patients who had underwent TAVR between February 2013 and March 2017 at Hacettepe University Adult Hospital Cardiology Clinic. Results . Total number of incidental diagnoses was 541, and 451 of them were the first diagnoses. Total number of cardiovascular findings and noncardiovascular findings was 369 and 172, respectively. The most common cardiovascular finding is atherosclerotic heart disease (139, 89.6%). The most common noncardiovascular finding is pulmonary nodule (41, 26.4%). 143 of 155 patients had at least one incidental diagnosis after the reassessment, and 33 different diagnoses were identified with computed tomography. The mean STS-PROM was 8.38% (range 2.8% to 23%), and the mean STS-PROM was calculated 9.4% (range 3.6% to 23%) after the reassessment of computed tomography. Conclusion . Preprocedural evaluation is one of the most important steps in TAVR. Computed tomography imaging provides extensive information, not only for procedure planning. Our findings emphasize that computed tomography has a crucial role for the preprocedural evaluation of TAVR candidates.